2005
DOI: 10.1074/jbc.m501707200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Mammalian Target of Rapamycin (mTOR) at Ser-2448 IsMediated by p70S6 Kinase

Abstract: The mammalian target of rapamycin (mTOR) coordinates cell growth with the growth factor and nutrient/ energy status of the cell. The phosphatidylinositol 3-kinase-AKT pathway is centrally involved in the transmission of mitogenic signals to mTOR. Previous studies have shown that mTOR is a direct substrate for the AKT kinase and identified Ser-2448 as the AKT target site in mTOR. In this study, we demonstrate that rapamycin, a specific inhibitor of mTOR function, blocks serum-stimulated Ser-2448 phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
345
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(378 citation statements)
references
References 37 publications
(38 reference statements)
22
345
1
4
Order By: Relevance
“…The level of p-p70S6K on Thr421/Ser424, showed a pattern similar to p-p70S6K on Thr389. We also found that the phosphorylation of mTOR at Ser-2448, which was reported to be the target of p70S6 kinase, 18 was reduced as well. Propionate also inhibited mTOR pathway in SW480 cells (Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 57%
“…The level of p-p70S6K on Thr421/Ser424, showed a pattern similar to p-p70S6K on Thr389. We also found that the phosphorylation of mTOR at Ser-2448, which was reported to be the target of p70S6 kinase, 18 was reduced as well. Propionate also inhibited mTOR pathway in SW480 cells (Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 57%
“…This lack of clear correlation in activation among mTOR cassette proteins presumably arises from the convergence of multiple signaling pathways involving mTOR. 9 For example, mTOR can be phosphorylated by other protein kinases, in addition to Akt, 12,34 and the mTOR substrates, S6K and 4E-BP1, can be phosphorylated by Erk1/2. 35 Moreover, signaling pathways are often not unidirectional and may be subject to feedback signaling.…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, signaling pathways are often not unidirectional and may be subject to feedback signaling. Examples include mTOR activation by p-S6K, 34 and Akt inhibition by mTOR. 10 It is also important to note that activation of these signaling molecules may be transient and simultaneous activation of linked kinases may be difficult to detect in many tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…One downstream molecule of mammalian target of rapamycin (mTOR) is ribosomal S6 kinase (p70S6K). This kinase regulates the efficiency of translation of certain mRNAs and also functions in a negative feedback loop to control Akt activity (Chiang and Abraham, 2005;Inoki et al, 2005;Martelli et al, 2007). Akt, mTOR and p70S6K activation have been associated with a more severe prognosis in breast and other cancers (Bose et al, 2002;Clark et al, 2002;DeGraffenried et al, 2004;Nagata et al, 2004;Lin et al, 2005;Tsutsui et al, 2005a, b;Klos et al, 2006;Tokunaga et al, 2006;Martelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%